2011
DOI: 10.5350/dajpn2011240403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation, validity and reliability of the Leahy Emotional Schema Scale Turkish version based on Turkish university students and workers / Üniversite öğrencileri ve çalışanları örnekleminde Leahy Duygusal Şema Ölçeği’nin Türkçe uyarlaması, geçerlilik ve güvenilirliği

Abstract: Adaptation, validity and reliability of the Leahy Emotional Schema Scale Turkish version based on Turkish university students and workers Objective: Emotional schema concept is developed for determining beliefs and attributions about emotions. The aim of this study was to examine validity and reliability of the Turkish version of "Leahy Emotional Schema Scale" (LESS). Method: The sample consisted of 436 participants including students, workers and their relatives from various faculties of two Turkish universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In a study by Yavuz et al, it was shown that making sense of emotions and accepting emotions were beneficial in improving anxiety and depression [18]. In our study, the fact that people who use the Acceptance of Emotions schemas have less anxiety symptoms supports the literature [9] and it is seen as the first step towards change and treatment for people to accept and understand their symptoms and emotions [9].…”
Section: Emotional Schemassupporting
confidence: 77%
See 3 more Smart Citations
“…In a study by Yavuz et al, it was shown that making sense of emotions and accepting emotions were beneficial in improving anxiety and depression [18]. In our study, the fact that people who use the Acceptance of Emotions schemas have less anxiety symptoms supports the literature [9] and it is seen as the first step towards change and treatment for people to accept and understand their symptoms and emotions [9].…”
Section: Emotional Schemassupporting
confidence: 77%
“…The Denial of Emotions and Emotional Weakness, which are emotional schemas, are not present in the original form of the scale, only in the Turkish version. Yavuz et al, who conducted the validity and reliability study in Turkish, stated that cultural characteristics were at the forefront of these subgroups [18]. Although denial of emotions was higher in patients with high anxiety symptoms, as expected, our study showed that denial of emotions had a reducing effect on the occurrence of anxiety symptoms.…”
Section: Emotional Schemassupporting
confidence: 73%
See 2 more Smart Citations
“…In some studies, a composite score of LESS called "Negative Beliefs of Emotions" is used by adding the subscales scores (16). The reliability and validity study of the LESS-T was conducted by Yavuz et al (20), who reported the alpha coefficient to be 0.86 for the total scale, which includes 14 subdimensions. Emotional avoidance, weakness, view of emotions as harmful, discrepancy, and denial of emotions have been demonstrated in the Turkish version of the scale.…”
Section: Leahy Emotional Schema Scale Turkish Version (Less-t)mentioning
confidence: 99%